Scattering amplitudes using twistor strings - Lize, Matheus Loss [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Neste trabalho revisamos as amplitudes de MHV no contexto da teoria de super-Yang-Mills. Nós estudamos as simetrias das amplitudes de MHV no espaço de twistors como uma motivação para introduzir a teoria de cordas com twistors . A teoria de cordas com twistors feita por Nathan Berkovits [3] é revisada e uma fórmula geral é dada para calcular amplitudes de espalhamento com n gluons. No final, a partir desta fórmula deduzimos a amplitude de MHV.

In this work we review the maximal helicity violating (MHV) scattering amplitude in the context of super-Yang-Mills theory. We study the symmetries of the MHV amplitude in the twistor space as a motivation to introduce the twistor string theory. The twistor string action introduced by Nathan Berkovits [3] is reviewed and also a general formula is given for the scattering amplitude with n gluons. In the end, the MHV amplitude is derived from this formula.
Amplitudes de espalhamento usando cordas no espaço de twistors
Keywords: Super Cordas; Amplitude de MHV; Superstring; MHV amplitudes; Twistors